Un Problema de Enrutamiento del Vehículo con Enfoque de Ventanas de Tiempo para Mejorar el Proceso de Entregas - Pineda Zapata, Uriel; Carabalí Ararat, Hader (Ingeniería, 2020)
Context: This paper proposes to solve the problem of accumulated deliveries, identified in 2018, in a company dedicated to the service of deliveries of packages and merchandise, located in Valle del Cauca, Colombia, based on the optimization of the logistics process that allows reducing delivery times to customers and avoiding wastages for the company. This means generating appropriate routes, according to the classic problem called Vehicle Routing Problem (VRP). Método: The information of more than 200 clients is analyzed for its realization. Quality tools, such as Pareto analysis and process approach, were combined with optimization techniques based on the Clarke Wright method and the use of time windows through the VRP Solver 3.0 program. Resultados: With the design of the routes proposed to meet the deliveries of one of the areas with the highest demand in the company (Central Zone), the results of the simulation showed an increase in the service level of 60%, given the use of the vehicle to the distribution in a complete working day and not only in half day of work. It is evident that the increase in customers served generates additional income, sufficient to cover the costs of using the vehicle half working day more, with profits for the company. Likewise, the delivery capacity, in Tm, is increased by 39%. So the accumulated merchandise by delivery is eliminated. Conclusiones: With the use of time windows, a method for route programming is proposed by applying the VRP Solver 3.0 tool, more consistent with the daily operation of logistics operators as the case studied. Likewise, this article constitutes a way of bringing the theoretical knowledge of the academy to the efficient management of the service in SMEs. Thus, companies like the case presented, can further improve their service level with appropriate technologies for the processing and control of customer information, with the purpose to planning the deliveries.